Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: If a(3)=x, then a(1)=? [#permalink]
02 Mar 2012, 20:29

Expert's post

The sequence a_1, a_2, …, a_n, … is such that a_n=4a_{n-1}-3 for all integers n>1. If a_3=x, then a_1=? A. 4x–3 B. 16x–15 C. (x+3)/4 D. (x+3)/16 E. (x+15)/16

Since, a_n=4a_{n-1}-3 then a_3=4a_{2}-3 --> x=4a_{2}-3 --> a_2=\frac{x+3}{4}.

Or substitute the value for x, say x=5, then a_3=5=4a_{2}-3 --> a_2=2 --> a_2=2=4a_{1}-3 --> a_1=\frac{5}{4}. Now, just plug x=5 in the answer choices and see which one yields \frac{5}{4}: only E.

Answer: E.

Note that for plug-in method it might happen that for some particular number(s) more than one option may give "correct" answer. In this case just pick some other numbers and check again these "correct" options only. For example if you pick x=1 then you get three "correct" options A, C and E. Generally -1, 0, and 1 are not good choices for plug-in method.

Re: If a(3)=x, then a(1)=? [#permalink]
02 Mar 2012, 20:34

The sequence a(1), a(2), …, a(n), … is such that a(n)=4a(n–1) –3 for all integers n>1. If a(3)=x, then a(1)=?

My Line of thought: 1. What is given to me a(3)=x, and formula. 2. I need to express a(1) from known. 3. a(n) can be expressed as a(n-1) means it can be expressed by any of the predecessor or successor. as a(n-1) can be expressed as a(n-2)....hence a(n) can be expressed as a(n-2) and vice versa 4. a(3) = 4a(2)-3 , (n=3)>1 = 4 [4a(1)-3]-3 , (n=2)>1 =16a(1)-12-3 x = 16a(1)-15 (x+15)/16 = a(1) == Ans E _________________